Impaired Health-Related Quality of Life in Adolescent Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: The Impact of Core Symptoms - Roma, Maria; Marden, Colleen L.; Flaherty, Marissa A. K.; Jasion, Samantha E.; Cranston, Erica M.; Rowe, Peter C. (Frontiers in Pediatrics, 2019)
Objective: The objectives of this study were to compare the health-related quality of life (HRQOL) of a North American population of adolescents and young adults with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) to (1) healthy controls (HC), (2) adolescents with ME/CFS in other countries, and (3) other forms of pediatric chronic illness, and (4) to examine the influence of the core illness symptoms in the Institute of Medicine (IOM) case definition on impaired HRQOL. Study design: Cross-sectional study comparing individuals with ME/CFS referred to a tertiary care Chronic Fatigue clinic and HC. Eligible participants were age 10-30 years and met the Fukuda criteria for CFS. HC were eligible if they were age 10-30 years, with self-reported good, very good, or excellent general health. Pediatric HRQOL was measured using the PedsQL (Pediatric Quality of Life Inventory) and other validated instruments. Results: We enrolled 55 consecutive ME/CFS patients (46 F) aged 10-23 years. From a pool of 69 potential HC we selected 55 with similar age and gender distribution for comparison. The total and subscale scores on the PedsQL and on all other measures of HRQOL indicated significantly worse function among those with ME/CFS (all P < 0.001). The self-reported frequency of post-exertional malaise (PEM) was significantly associated with the severity of impaired HRQOL (P < 0.001). Cognitive impairment had a weaker association with the PedsQL score (P=0.02). Orthostatic intolerance was present in 96% of the ME/CFS population. Of the 55 who satisfied the Fukuda criteria, 47 (85%) also satisfied the IOM criteria for the diagnosis. Those meeting the IOM criteria had worse PedsQL total scores than those meeting just the Fukuda criteria (P < 0.001). Conclusions: HRQOL was substantially lower in an ambulatory population of adolescents and young adults with ME/CFS than for healthy controls in North America, consistent with reports from other continents. HRQOL was also lower in ME/CFS than has been described in children with asthma, diabetes mellitus, epilepsy, eosinophilic gastroenteritis, and cystic fibrosis. The findings of this study lend further support to the inclusion of PEM, cognitive impairment, and orthostatic intolerance as core symptoms of pediatric ME/CFS.